2020
DOI: 10.1111/bph.15136
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol consumption and sedation are altered in mice lacking the glycine receptor α2 subunit

Abstract: Background and Purpose The precise mechanism/s of action of ethanol, although studied for many years, are not well understood. Like other drugs of abuse, ethanol affects dopamine levels in the nucleus accumbens (nAc), an important region of the mesolimbic system, causing a reinforcing effect. It has been shown that glycine receptors (GlyRs) present in the nAc are potentiated by clinically relevant concentrations of ethanol, where α1 and α2 are the predominant subunits expressed. Experimental Approach Using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 69 publications
3
17
0
Order By: Relevance
“…While Western blot analysis showed no significant changes in global α subunit levels in the nAc in Glra3 −/− mice, the results showed a significant decrease in GlyR β subunits in the knockout mice. These results indicate that deletion of Glra3 only slightly reduced the presence of the α subunit pool in the nAc, thus suggesting the presence of a lower level of α3 as compared to α1 and α2 (Forstera et al, 2017;San Martin et al, 2020;Gallegos et al, 2021). However, the data does not allow us to rule out the possibility that compensatory up-regulation of α subunits occurred in the Glra3 −/− mice.…”
Section: Role Of Glyr α3 Subunits In Nucleus Accumbens Neuronsmentioning
confidence: 70%
See 4 more Smart Citations
“…While Western blot analysis showed no significant changes in global α subunit levels in the nAc in Glra3 −/− mice, the results showed a significant decrease in GlyR β subunits in the knockout mice. These results indicate that deletion of Glra3 only slightly reduced the presence of the α subunit pool in the nAc, thus suggesting the presence of a lower level of α3 as compared to α1 and α2 (Forstera et al, 2017;San Martin et al, 2020;Gallegos et al, 2021). However, the data does not allow us to rule out the possibility that compensatory up-regulation of α subunits occurred in the Glra3 −/− mice.…”
Section: Role Of Glyr α3 Subunits In Nucleus Accumbens Neuronsmentioning
confidence: 70%
“…This unchanged duration of LORR in Glra3 −/− mice is consistent with previous published findings (Blednov et al, 2015) and might support a more restricted localization of α3 subunits in the CNS unable to produce a sedative action. On the other hand, previous studies have demonstrated that α1 and α2 subunits are important for the sedative effects of ethanol (Aguayo et al, 2014;San Martin et al, 2020;Gallegos et al, 2021). Thus, these findings suggest that α1 and α2 subunits are more relevant than α3 subunits in terms of alcohol effects on GlyRs in the CNS.…”
Section: Role Of Glyr α3 Subunits In Nucleus Accumbens Neuronsmentioning
confidence: 71%
See 3 more Smart Citations